Laparoscopic Cholecystectomy- A Safe treatment option for Gangrenous Cholecystitis 48 and Empyema Gallbladder in experienced hands (Journal of Surgical Sciences, 2019)
Background: Laparoscopic cholecystectomy has become the gold standard of treatment for gall stone disease and in acute cholecystitis. But controversy persists regarding laparoscopic approach to gangrenous gallbladder and empyema gallbladder due to the risk of life threatening complications. We share our experience in a tertiary care multidisciplinary diabetic hospital where we encounter significant number of patients with empyema Gallbladder and gangrenous gallbladder because most of our patients are diabetic and hence immunocompromised. Purpose of this study was to evaluate the safety of laparoscopic procedure for the treatment of empyema of gallbladder and gangrenous gallbladder in an experienced hand.Methods & Materials: Between January 2013 and January 2015 we performed 1191 cases of laparoscopic cholecystectomy. Empyema gallbladder and gangrenous gallbladder were found per operatively in 345 and 53 cases respectively.All were managed by laparoscopic procedure except two cases, where conversion to open cholecystectomy was needed.Result: The mean operating time was 72 minutes(45-100 minutes) in empyema gallbladder. In gangrenous cholecystitismean operating time was 80 minutes(60-100 minutes). Total number of patients (including empyema gallbladder 345 and gangrenous cholecystitis 53) were 398. Among them 52 patients (13%) had excessive bleeding(>100ml) from calot’s triangle or gallbladder bed in liver. Spillage of stones occurred in 28 patients (7%). 1 patient had common bile duct injury (.25%). Gallbladder retrieval was difficult in 71 patients (18%). In the post operative period 21 patient (5%) developed minor port infection in the umbilical port. 9 patients (2%) developed chest infection, and 1 patient (.25%) developed MI. 356 patients (89%) were discharged within 72 hours of surgery.Conclusions: Innovative technique, appropriate instruments, knowledge about the possible risks and way to manage them, with expertise in intracorporeal suturing and knotting are an essential pre requisites to attempt these cases. Operating time is more but post operative recovery is prompt. Hospital stay is significantly less than open cholecystectomy. Laparoscopic cholecystectomy is a safe procedure in cases of Empyema and gangrenous gallbladder, provided the surgeon is experienced enough and has a low threshold to convert to open cholecystectomy at anypoint of time.Journal of Surgical Sciences (2015) Vol. 19 (2) : 48-51